The contribution of phenotypic plasticity to complementary light capture in plant mixtures. Issue 4 (21st April 2015) - Zhu, Junqi; van der Werf, Wopke; Anten, Niels P. R.; Vos, Jan; Evers, Jochem B.
Summary Interspecific differences in functional traits are a key factor for explaining the positive diversity–productivity relationship in plant communities. However, the role of intraspecific variation attributable to phenotypic plasticity in diversity–productivity relationships has largely been overlooked. By taking a wheat (Triticum aestivum)–maize (Zea mays) intercrop as an elementary example of mixed vegetation, we show that plasticity in plant traits is an important factor contributing to complementary light capture in species mixtures. We conceptually separated net biodiversity effect into the effect attributable to interspecific trait differences and species distribution (community structure effect), and the effect attributable to phenotypic plasticity. Using a novel plant architectural modelling approach, whole‐vegetation light capture was simulated for scenarios with and without plasticity based on empirical plant trait data. Light capture was 23% higher in the intercrop with plasticity than the expected value from monocultures, of which 36% was attributable to community structure and 64% was attributable to plasticity. For wheat, plasticity in tillering was the main reason for increased light capture, whereas for intercropped maize, plasticity induced a major reduction in light capture. The results illustrate the potential of plasticity for enhancing resource acquisition in mixed stands, and indicate the importance of plasticity in the performance of species‐diverse plant communities.